An Empirical of Supply Chain Management Strategy as Mediation on Organizational and Operation Performance: A Study on Indonesia’s Retail Shops - J.E. Sutanto (International Journal of Supply Chain Management, 2021)
According to the Indonesian Retail Entrepreneurs Association, the retail business or retail business in Indonesia has continued to develop in the last five years in line with the growth of the Indonesian economy. The retail industry is defined here as an industry that sells products and services that have been added value to meet the needs of individuals, families, groups or end users. Besides that, the retail industry in Indonesia provides a large contribution to the Gross Domestic Product and also absorbs a large number of workers. Purpose, An empirical of supply chain management strategy as mediation on organizational and operation performance: a study on Indonesia’s retail shops. Methodology/approach, the study sample consists of 175 companies operating in retail shops in East Java. As a standard research instrument, it was used as the data collection was used as the data collection, which was distributed to the managers or supervisors of retail shops. Findings, the results of hypothesis testing have a positive and significant effect on supply chain management strategy as mediation on organizational and operation performance of supply chain at retail shops. Research limitations, it was found that supply chain management strategy has a mediating role in the relationship on supply chain organizational and supply chain operation performance at retail shops. Originality, the results of this study will directly increase the amount of literature related to innovation in supply chain management implementation